Key performance indicators : the 75 measures every manager needs to know - Marr, Bernard. 4 0 16; 5 (Harlow, England ;;New York : Pearson Financial Times Publishing, 2012)
Performance indicators are essential tools which will tell you if your business is on target or veering off course. Using the right indicators will help you deliver the right results. This book cuts straight to the 75 KPIs that matter. It explains what key performance indicators are, gives you short overviews of each metric and describes how to use the measure effectively. There are worked examples throughout which will equip you with the skills to understand, assess and interpret the most important aspects of any business. From net profit margin, to customer satisfaction through to brand quality, six sigma and employee engagement, this book gives you the manageable and essential key indicators.--Back cover.
Introduction -- Part one Financial perspective -- Net profit -- Net profit margin -- Gross profit margin -- Operating profit margin -- EBITDA -- Revenue growth rate -- Total shareholder return (TSR) -- Economic value added (EVA) -- Return on investment (ROI) -- Return on capital employed (ROCE) -- Return on assets (ROA) -- Return on equity (ROE) -- Debt-to-equity (D/E) ratio -- Cash conversion cycle (CCC) -- Working capital ratio -- Operating expense ratio (OER) -- CAPEX to sales ratio -- Price/earnings ratio (P/E ratio) -- Part two Customer perspective -- Net promoter score (NPS) -- Customer retention rate -- Customer satisfaction index -- Customer profitability score -- Customer lifetime value -- Customer turnover rate -- Customer engagement -- Customer complaints -- Part three Marketing and sales perspective -- Market growth rate -- Relative market share -- Brand equity -- Cost per lead -- Conversion rate -- Search engine rankings (by keyword) and click-through rate -- Page views and bounce rates -- Customer online engagement level -- Online share of voice (OSOV) -- Social networking footprint -- Klout score -- Part four Operational processes and supply chain perspective -- Six Sigma level -- Capacity utilisation rate (CUR) -- Process waste level -- Order fulfilment cycle time (OFCT) -- Delivery in full, on time (DIFOT) rate -- Inventory shrinkage rate (ISR) -- Project schedule variance (PSV) -- Project cost variance (PCV) -- Earned value (EV) metric -- Innovation pipeline strength (IPS) -- Return on innovation investment (ROIp2s) -- Time to market -- First pass yield (FPY) -- Rework level -- Quality index -- Overall equipment effectiveness (OEE) -- Process or machine downtime level -- First contact resolution (FCR) -- Part five Employee perspective -- Human capital value added (HCVA) -- Revenue per employee (RPE) -- Employee satisfaction index -- Employee engagement level -- Staff advocacy score -- Employee churn rate -- Average employee tenure -- Absenteeism Bradford factor -- 360-degree feedback score -- Salary competitiveness ratio (SCR) -- Time to hire -- Training return on investment -- Part six Corporate social responsiblity perspective -- Carbon footprint -- Water footprint -- Energy consumption -- Savings levels due to conservation and improvement efforts -- Supply chain miles -- Waste reduction rate -- Waste recycling rate -- Product recycling rate.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Management. -- Performance technology;Performance standards.;Organizational effectiveness. -- 20; 20; 2